Genetic Variants in the Vitamin D Receptor Gene Increase the Risk of Urinary Tract Infection in a Southeast Population of Iran: A Case-control Study - Sadeghi Bojd, Simin; Kashani, Sara; Eftekharzadeh, Mina; Heidari Nia, Milad; Naghavi, Anoosh (Journal of Pediatric Nephrology, 2025)
Background and Aim: Urinary tract infection (UTI) is a common infection affecting children. Besides microorganism pathogens, genetic background plays a pivotal role in the pathogenesis of diseases. Vitamin D receptor (VDR) plays a crucial role in the pathogenesis of some cancers and infectious diseases. This study aimed to evaluate the association between polymorphisms in the VDR gene and risk of UTI. Methods: In the current study, 127 children affected by UTI were referred to the pediatric nephrology clinic in Zahedan, and 100 subjects with no history of infection were genotyped. The genotyping was carried out by restriction fragment length polymorphism-polymerase chain reaction (RFLP-PCR). SPSS software, version 22.0 was used for statistical analysis. Results: The results revealed that rs2228570C>T (FokI), rs7975232A>C (ApaI), and rs731236T>C (TaqI) increased the risk of UTI, whereas rs1544410G>A (BsmI) decreased the risk of the disease. Conclusion: The results suggest that the genetic variants in the VDR gene may play a role in the pathogenesis of UTI.